The Urgency of Using Syariah Method Facing Economic Crisis : to Compare with Conventional Method - Nadya Puteri Andreza; Abdul Adhim Mustaqim; Fadia Fitriyanti (Law and Justice, 2021)
The global economic crisis has resulted in various global financial institutions experiencing losses and bankruptcy. The recurring global financial crisis in the world requires solutions to be resolved and prevented. The global economic crisis has resulted in various global financial institutions experiencing losses and bankruptcy. The perfect Islamic Sharia is able to provide a way out of the grip of the global economic crisis that has hit many countries today. The Islamic economy is one of the significant steps the government must take in dealing with negative spreads and the vulnerability of the global economy. Sharia banking is considered to be more crisis resistant than conventional banking if economic conditions deteriorate. This is because Islamic banking is more flexible in dealing with any situation. Islamic banking is increasingly recognized in the community from day to day. Not only for Muslims, but also for those who are non-Muslims. This study aims to determine the Islamic economy as the best solution in solving the problem of the global economic crisis. The data used in this research is secondary data. The results of this study indicate that the Islamic economy is a solution to the global economic crisis. Islamic banking can help in overcoming the burden of the crisis in the short term and also in the future.